Ocena działalności reasekuracyjnej zakładów ubezpieczeń działających na rynku polskim - Jędrzychowska, Anna; Poprawska, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents selected indices, that are helpful in analysis of reinsurance policy in insurances companies. Analyzing and controlling quality of reinsurance is important either for insurances companies or organs of oversights and rating's agencies. That is why it is worth counting their values for polish insurance's companies and performing their juxtaposition and analyses. It has shown on extracting conclusion concerning individual underwriter and policy of reinsurance plant of Polish insurance (insurance property). Figures for review include years 2001-2005. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 129-142